OPTIMASI FORMULA TABLET HISAP EKSTRAK RIMPANG LENGKUAS (Alpinia galanga (L.) Stuntz) DENGAN KOMBINASI BAHAN PEMANIS MANITOL DAN SUKROSA MENGGUNAKAN METODE SIMPLEX LATTICE DESIGN - Duhita Aufiya; Suwijiyo Pramono; Mufrod Mufrod (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
Galangal (Alpinia galanga (L.) Stuntz) has many benefits for the health. Galangal is used as a tonic traditionally, but the dose is unknown, so it is necessary to be formulated. Lozenges was selected for the formulation of galangal because its practical and comfortable form. Taste is an important parameter for the lozenges so a mixture of mannitol and sucrose are used in this formulation. This research aims to optimize the lozenges formulation using a mixture of mannitol and sucrose with Simplex Lattice Design method. Galangal rhizome was extracted by maceration using 70% ethanol. Lozenges were made in three formulas, Formula A (100%: 0%), Formula B (50%: 50%), and Formula C (0%: 100%) with SLD in wet granulation method. Granule mass was sieved through the sieve no. 10 and dried in an oven at 60°C, then dried granule was mixed homogeneously with magnesium stearate-talk and tested for its physical properties include flow rate and compactibility. The granule was compressed into tablets and tested for its physical properties, including weight uniformity, hardness, friability, dissolving time, and tasting test. The data which was obtained were used to create a profile of physical properties of the granule and the taste of the tablet. Optimum formula was selected based on the highest total response. The tablet was created based on the optimum formula and tested physical properties of granule and tablets. The data was obtained and compared theoritically and statistically using the T-Test. The result showed that optimum formula of galangal rhizome extract lozenges is a formula with ratio 25% maintol : 75% sucrose. The optimum formula of the flow rate and granule compactibility and significantly different between verification and SLD calculations, while the dissolved time and the respon of tablets flavor are not significantly different. The dominant composition of sucrose can increase granule's compactibility response, dissolving time, and tasting test of lozenges, lowering the response speed of the flow of granules.